2024
DOI: 10.3389/fimmu.2024.1373435
|View full text |Cite
|
Sign up to set email alerts
|

Cannabidiol exerts multitarget immunomodulatory effects on PBMCs from individuals with psoriasis vulgaris

Cristina Pagano,
Elena Ciaglia,
Laura Coppola
et al.

Abstract: IntroductionThe involvement of endocannabinoid system (ECS) in the inflammatory cascade, and the ability of phytocannabinoids, endocannabinoids and their synthetic analogues to modulate it has become an interesting research area for new therapeutic approaches in inflammatory skin diseases. Cannabidiol (CBD) appears to be the most promising among phytocannabinoids, due to the lack of psychotropic effects and low toxicity profile. Its anti-inflammatory action has been highlighted in different preclinical models,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Specifically, it has been observed that CBD reduces the secretion of inflammatory cytokines such as IFNγ and TNFα in peripheral blood mononuclear cells (PBMCs) from individuals with psoriasis, which are key factors in the disease’s pathophysiology. 20 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, it has been observed that CBD reduces the secretion of inflammatory cytokines such as IFNγ and TNFα in peripheral blood mononuclear cells (PBMCs) from individuals with psoriasis, which are key factors in the disease’s pathophysiology. 20 …”
Section: Introductionmentioning
confidence: 99%
“…Specifically, it has been observed that CBD reduces the secretion of inflammatory cytokines such as IFNγ and TNFα in peripheral blood mononuclear cells (PBMCs) from individuals with psoriasis, which are key factors in the disease's pathophysiology. 20 Additionally, CBD has demonstrated potential in minimizing oxidative stress in keratinocytes from psoriatic skin, which could help avert the metabolic effects related to peroxidation. This beneficial action may stem from CBD's capability to influence the activity of enzymes that promote pro-oxidative conditions and to bolster the antioxidant defenses in these cells.…”
Section: Introductionmentioning
confidence: 99%